2011
DOI: 10.1111/j.1474-9726.2011.00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of ghrelin receptor reduces adiposity and improves insulin sensitivity during aging by regulating fat metabolism in white and brown adipose tissues

Abstract: Summary Aging is associated with increased adiposity in white adipose tissues and impaired thermogenesis in brown adipose tissues; both contribute to increased incidences of obesity and type 2 diabetes. Ghrelin is the only known circulating orexigenic hormone that promotes adiposity. In this paper, we show that ablation of the ghrelin receptor (growth hormone secretagogue receptor, GHS-R) improves insulin sensitivity during aging. Compared to wild-type (WT) mice, old Ghsr−/− mice have reduced fat and preserve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
194
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(221 citation statements)
references
References 51 publications
24
194
0
3
Order By: Relevance
“…Furthermore, the results reported in this study, as shown in Table 2, are in agreement with those of Lin et al (2011) who reported less food intake in mice with ablation of ghrelin receptor. Nevertheless, the results observed in this study with respect to decreased feed intake in chickens, given in Table 2, contradict those of Vizcarra et al (2012), who studied active immunization of ghrelin in turkeys.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, the results reported in this study, as shown in Table 2, are in agreement with those of Lin et al (2011) who reported less food intake in mice with ablation of ghrelin receptor. Nevertheless, the results observed in this study with respect to decreased feed intake in chickens, given in Table 2, contradict those of Vizcarra et al (2012), who studied active immunization of ghrelin in turkeys.…”
Section: Discussionsupporting
confidence: 92%
“…They maintained that changes in glycemic control attributed to infusion of GHS-R antagonist might cause less food intake and weight gain (Asakawa et al, 2003). In another study, Lin et al (2011) mentioned that ablation of ghrelin receptor may cause less food intake and reduce adiposity in mice. In a study on growing pigs (Vizcarra et al, 2007), after active immunization against ghrelin, reduced feed intake (mild anorexia) and body weight gain were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest alternative pathways for lipid metabolism involving peripheral actions of ghrelin. The presence of functional GHSR1a has been demonstrated in adipocytes by pharmacological, physiological, and genetic studies (16,17). Both GHSR1a-dependent and GHSR1a-independent mechanisms have been reported to mediate the effects of ghrelin on adipogenesis and lipid metabolism in adipocytes (6,18).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that BAT exerts anti-type 2 diabetic effects associated with improvements of dyslipidemia and insulin secretion (de Souza et al 1997;Peirce and Vidal-Puig 2013). Moreover, recent studies on rodents have showed that caloric restriction postpones the age-related decline in BAT mitochondrial function (Valle et al 2008) and ghrelin ablation in older individuals prevents age-associated decline in UCP1 gene expression (Lin et al 2011). Therefore, it may be possible to prevent the age-related decrease BAT content and in consequence decelerate age-related fat mass accumulation and development of diabetes.…”
Section: Brown Adipose Tissuementioning
confidence: 99%